2014
DOI: 10.1139/cjc-2013-0486
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and hydrolytic stability of diorganotin(IV)bis(O-alkyl alkylphosphonate)s

Abstract: Diorganotinbis(O-alkyl alkylphosphonate)s, R 2 Sn(O 2 P(OR 1 )R 1 ) 2 [R 1 = Me, R = Me (1), Et (2), n-Bu (3); R 1 = Et, R = Me (4), Et (5), n-Bu (6)] have been synthesized from the reaction between dimethyl/diethyl/di-n-butyltin dichloride and dialkyl alkylphosphonates, (R 1 O) 2 P(O)R 1 , in a solvent-free medium (120°C, 18 h). X-ray crystal structure of 1 reveals two independent molecules in the unit cell that form one-dimensional polymeric motifs by virtue of bridging bidentate phosphonate groups. The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Zuckerman et al have reported the synthesis of cyclohexameric triphenyltin O -methylmethylphosphonate, [Ph 3 SnOP­(O)­(OCH 3 )­CH 3 ] 6 , by a series of complex steps involving the Arbuzov rearrangement of a Ph 3 SnOP­(OCH 3 ) 2 intermediate . Our contribution in this area relates to the synthesis of diorganotin bis­( O -alkylorganophosphonate)­s, R 2 Sn­{O­(P)­(O)­(OR)­R} 2 , and their H -phosphonate analogues from the direct reaction between diorganotin dichloride and the corresponding organophosphonic acid dialkyl ester/ H -phosphonic acid dialkyl ester. , The reaction proceeds via the selective cleavage of the (P)­O–C bond and the elimination of alkyl halide as the byproduct.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Zuckerman et al have reported the synthesis of cyclohexameric triphenyltin O -methylmethylphosphonate, [Ph 3 SnOP­(O)­(OCH 3 )­CH 3 ] 6 , by a series of complex steps involving the Arbuzov rearrangement of a Ph 3 SnOP­(OCH 3 ) 2 intermediate . Our contribution in this area relates to the synthesis of diorganotin bis­( O -alkylorganophosphonate)­s, R 2 Sn­{O­(P)­(O)­(OR)­R} 2 , and their H -phosphonate analogues from the direct reaction between diorganotin dichloride and the corresponding organophosphonic acid dialkyl ester/ H -phosphonic acid dialkyl ester. , The reaction proceeds via the selective cleavage of the (P)­O–C bond and the elimination of alkyl halide as the byproduct.…”
supporting
confidence: 86%
“…The result finds an analogy with an earlier report on the oxidative addition of phosphate esters on metallic zinc . The IR and NMR spectroscopic data of 1 (see the Supporting Information, SI) are identical with those of an authentic sample obtained from the reaction of dimethyltin dichloride with methylphosphonic acid dimethyl ester …”
mentioning
confidence: 99%
“…11 In continuation of our recent studies on the synthesis and structural aspects of diorganotin(IV) phosphonate esters, R 2 Sn {OP(O)(OMe)Me} 2 (R ¼ Me, Et), we have drawn our attention to a unique crystal growth behaviour of n-Bu 2 Sn{OP(O)(OMe)Me} 2 (1) which has been previously characterized by spectroscopic methods. 12 Upon evaporation induced crystallization of 1 from a solution in chloroform, bre-like crystallites of several microns in length were obtained. The phenomenon has also been observed in chloroform-acetonitrile and chloroformether solvent mixtures.…”
mentioning
confidence: 99%
“…The tin atoms in the polymeric chains adopt a distorted octahedral geometry with equatorial SnO 4 core [ P 360 AE 0 ] and trans n-butyl groups [:C-Sn-C ¼ 180.0(0) ] while other metrical parameters resemble closely with those reported earlier for analogous dialkyltinbis(O-methylmethylphosphonate)s. 12 The inorganic chains comprising of [-Sn-O-P-O-] 2 rings run along crystallographic a-axis while the presence of weak C-H/O hydrogen bonds is discernable along the crystallographic c-axis. The orientation of secondary interactions approximately orthogonal to the linear inorganic chains provides anisotropy in the crystals and nds a close analogy with several reported examples of organic molecules exhibiting bent phenomenon.…”
mentioning
confidence: 99%
“…The purpose of this conference was to bring together researchers whose interests span the chemistry of germanium, tin, and lead, and this collection of manuscripts reflects the diverse range of topics presented at the conference: from the synthesis of low coordinate molecules as illustrated in the work presented by Jones 1 and studies of the reactivity of these interesting species as reported by Růžička, 2 Tokitoh 3 Willem, 4 and Baines 5 to the synthesis of high coordinate supramolecular structures as demonstrated in the work of Reuter; 6,7,8 from muon spin spectroscopy of germanium radicals as studied by West 9 to nuclear magnetic resonance spectroscopy 4 of Sn(II) and Sn(0) complexes; from the synthesis of ternary metal clusters as reported by Molloy 10 to polymers and their model oligomers as synthesized by Foucher 11 and Weinert, 12 respectively. Saito, 13 Shankar, 14 and Uhlig 15,16 describe their research on the high yielding synthesis and extended structures of several important functional tin(IV) compounds. Finally, the elegant synthesis of a mixed Group 14 propellane was reported by Breher.…”
mentioning
confidence: 99%